Evaluation and Selection of Tower Crane Stabilization Control Systems Using a Multi-Criteria Decision-Making Approach - Tran, Duc Hieu (International Journal of Sustainable Construction Engineering and Technology, 2025)
This study applies the Choosing by Advantages (CBA) decision-making method to evaluate and select appropriate stabilization control systems (SCS) for retrofitting the KБ-235 tower crane. Recognizing the widespread use and inherent instability of legacy crane models under dynamic wind and load conditions, two SCS alternatives are compared: a Passive Stabilization Control System (PSCS) and an Active Stabilization Control System (ASCS). The evaluation incorporates both technical and operational factors, including responsiveness to load swing, wind resistance, installation complexity, maintenance, and system precision. Attributes of each alternative are assessed using expert-validated criteria, followed by the quantification of each system’s advantages (IoA). Cost versus IoA analysis reveals that although the ASCS demands higher investment, it delivers superior stability performance and safety outcomes, with an IoA approximately five times that of the PSCS. The method was validated using assumed values from industry literature and expert input. These findings support the integration of structured decision-making frameworks in construction engineering and provide practical insights for upgrading legacy lifting equipment in resource-constrained environments.